2005
DOI: 10.1111/j.1540-4560.2005.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Ageism and Ageist Language Across the Life Span: Intimate Relationships and Non‐intimate Interactions

Abstract: The possible effects of ageist language and ageism on the structure and function of intimate and non-intimate relationships have received significant attention from social scientists. Recent research grounded in communication accommodation theory (Giles, Mulac, Bradac, & Johnson, ) point toward the numerous consequences of both negative and positive attitudes toward ageing. Focusing specifically on health care settings, this article reviews recent theoretical positions and empirical findings that link ageist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 71 publications
1
56
0
10
Order By: Relevance
“…While there is certainly individual variability in patient preferences for the type of communication with a health care provider, there is no evidence that these attributes of interpersonal communication are preferred by older persons. Above and beyond the potentially negative emotional experience for older patients and family members in the face of a provider's "poor bedside manner," provider communication styles may have substantive negative health consequences for the patient (Nussbaum et al 2005). For example, one research study analyzing videotaped encounters between a physical therapist and an older patient found that distancing and indifferent behaviors (e.g., not smiling; looking away from the client) were related to more negative short-and long-term cognitive and physical health outcomes for the patient (Ambady 2002).…”
Section: Ageist Communication By Health Care Professionalsmentioning
confidence: 99%
“…While there is certainly individual variability in patient preferences for the type of communication with a health care provider, there is no evidence that these attributes of interpersonal communication are preferred by older persons. Above and beyond the potentially negative emotional experience for older patients and family members in the face of a provider's "poor bedside manner," provider communication styles may have substantive negative health consequences for the patient (Nussbaum et al 2005). For example, one research study analyzing videotaped encounters between a physical therapist and an older patient found that distancing and indifferent behaviors (e.g., not smiling; looking away from the client) were related to more negative short-and long-term cognitive and physical health outcomes for the patient (Ambady 2002).…”
Section: Ageist Communication By Health Care Professionalsmentioning
confidence: 99%
“…Age-related labels have the power to create and maintain the stigma associated with old age (Mautner, 2007;Nelson, 2002Nelson, , 2005Nussbaum, Pitts, Huber, Krieger, & Ohs, 2005;Nuessel, 1984;Palmore, 1999;Tornstam, 1992). Research indicates that labels associated with old age are primarily negative (Miller, Leyell, & Mazachek, 2004;Nelson, 2002Nelson, , 2005Nuessel, 1982;Schmidt & Boland, 1986).…”
Section: Age-related Stigma and Labelingmentioning
confidence: 99%
“…In fact, sexism, ageism, racism, classism, religious intolerance, and sexual orientation discrimination are among those most widely uncovered in prejudice literature. Some examples are as follows: sexist beliefs and rape proclivity (Thomae and Viki 2013), ageist beliefs and patronizing talk toward older adults (Nussbaum et al 2005), and racism, classism, and sexual prejudice coinciding with numerous antisocial acts ranging from apathy to hate crimes (See Hecht 1998 for overview). We recall these particular findings because of their actively aggressive underpinning and, thus, similarity to bullying as it is assessed herein.…”
Section: Intolerant Schemasmentioning
confidence: 98%